Assessing the Psychological Impact of Genetic Susceptibility Testing - Roberts, J. Scott (The Hastings Center report, 2019)
The expanded use of genetic testing raises key ethical and policy questions about possible benefits and harms for those receiving disease-risk information. As predictive testing for Huntington’s was initiated in a clinical setting, survey research posing hypothetical test scenarios suggested that the vast majority of at-risk relatives wanted to know whether they carried a disease-causing mutation. However, only a small minority ultimately availed themselves of this opportunity. Many at-risk individuals concluded that a positive test result would be too psychologically overwhelming. A substantial literature suggests that individuals are often more resilient than anticipated in coping with many different health-related stresses. Much of my own work in the field has been through the Risk Evaluation & Education for Alzheimer’s Disease study (REVEAL), a series of randomized clinical trials assessing the impact of genetic susceptibility testing on asymptomatic individuals at risk for Alzheimer’s disease. Our experience in developing and implementing four successive, multisite trials provides some potentially useful lessons for the field. More people will be asking for their personal genetic information. Better understanding will help us decide when access is appropriate and how best to disclose results in a manner that supports adjustment to test findings and promotes use of genetic information to improve human health.